Signet-ring cell carcinoma of the prostate mimicking primary gastric carcinoma. - Ben-Izhak, O. (1992)
A post mortem examination of a 70 year old man, who died three years after a poorly differentiated adenocarcinoma of prostate had been diagnosed, showed widespread signet-ring cell carcinoma, with an associated linitis plastica. The signet-ring cells stained positively with prostatic specific antigen and with prostatic specific acid phosphatase, but failed to react with mucopolysaccharide staining. The electron microscopic appearance of the signet-ring cell tumour was due to the presence of large cytoplasmic vacuoles. This case emphasises the possibility that cases of metastatic signet-ring cell carcinoma may be prostatic in origin. This can be confirmed by specific immunohistochemical studies.